SWOT Research on the Development of Rural Tourism E-Commerce System under the Background of Big Data Era - Minglong Zhao (Hindawi Limited, 2021)
Economic development has gradually made tourism one of the most common options for people’s leisure and entertainment. The fast-paced life and heavy pressure in the city have made the relaxed and comfortable rural tourism sought after by many people. In our country, many villages have rich tourist attractions and unique cultural heritage, but they have not been fully developed due to information obstruction. Now, the advancement of Internet technology has made e-commerce, an emerging trade method, more closely related to rural tourism. Based on the background of big data, this paper has launched a research on the SWOT analysis of the development of rural tourism e-commerce system. Starting from the advantages, disadvantages, opportunities, and threats of the tourism e-commerce system, this paper discusses the necessity of combining rural tourism and e-commerce platforms in the Internet era, combining various internal and external conditions. From the perspective of the e-commerce system, all kinds of special features in the countryside can be transformed into product selling points on the platform to attract tourists, and the promotion of tourism revenue through the platform can further promote the continuous improvement of the rural tourism industry and form a virtuous circle. According to our data from the China Tourism Administration and related tourism statistics, the number of rural tourists in my country has increased from 630 million in 2011 to 3.13 billion in 2019, and the increase in rural tourism revenue has also reached 4.3 times. In order to prevent the rural backward marketing strategy from hindering the development of rural tourism, the introduction of a tourism e-commerce platform is a very necessary choice.